1993
DOI: 10.4267/2042/26420
|View full text |Cite
|
Sign up to set email alerts
|

Conservation et germination des semences

Abstract: Les graines de Sorbus torminalis sont les moins connues à l'intérieur du genre Sorbus. En revanche, les graines de Sorbus aucuparia ont déjà, en 1928 et 1931, fait l'objet d'études sur la dormance par Flemion. C'est d'ailleurs cette espèce qui a permis de mettre en évidence le comportement dormant des graines de Rosacées. Les recherches menées au Laboratoire de Semences forestières sur les graines d'Alisier torminal ont porté sur la conservation et la dormance. En effet, pour répondre aux besoins des praticien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Few fully formed seeds are produced, and the viability of seed collected is usually low; Willmot () found that only 5% of seed tested in Derbyshire were fertile. However, viability of sorted sound seed can easily be >60% and reach 94–97% (Muller & Laroppe ; Oršanić et al . ; Var, Bekci & Dinçer ).…”
Section: Floral and Seed Charactersmentioning
confidence: 99%
See 4 more Smart Citations
“…Few fully formed seeds are produced, and the viability of seed collected is usually low; Willmot () found that only 5% of seed tested in Derbyshire were fertile. However, viability of sorted sound seed can easily be >60% and reach 94–97% (Muller & Laroppe ; Oršanić et al . ; Var, Bekci & Dinçer ).…”
Section: Floral and Seed Charactersmentioning
confidence: 99%
“…Nevertheless, seeds can cope with some drying as germination of S. torminalis was found to be similar after 2 years whether stored at 4 or −5 °C and 7, 8 or 10% moisture (Muller & Laroppe ). Dormancy can be re‐induced by exposure of hydrated seeds to 20–25 °C (Muller & Laroppe ). Further details of seed storage, sowing depth and other in vivo recommendations can be found in Barnola, Durand & Parmentier (), Drapier (1993b), Kausch‐Blecken von Schmeling (), Muller & Laroppe () and Kausch‐Blecken von Schmeling & Kellner ().…”
Section: Floral and Seed Charactersmentioning
confidence: 99%
See 3 more Smart Citations